Assessing Marine Reserve Effects on Limpet Diversity and Abundance in Rock Pools along The Eastern Cape Coast of South Africa - Motebang DV Nakin; Munetsi Zvavahera (Universitas Airlangga, 2026)
Overexploitation of coastal marine resources driven by rapid human population growth has increased pressure on wild marine species. Marine reserves have been established along the South African coast to mitigate these impacts; however, their effects on macroinvertebrate communities, particularly limpets inhabiting rock pools along the Eastern Cape coast, remain poorly understood. This study assessed the abundance and diversity of limpets in rock pools within marine reserves and adjacent non-reserve areas to evaluate the ecological benefits of protection and biodiversity distribution across intertidal microhabitats. Sampling was conducted over 12 months at four sites: two marine reserves (Dwesa-Cwebe and Hluleka Nature Reserves) and two non-reserves (Nqabara and Presley’s Bay). At each site, rock pools were sampled across three shore zones (mid-low, mid-high, and high shore). Data were analysed using PRIMER v7 and Statistica v14.1. Limpet diversity was estimated using Shannon’s Diversity Index, while abundance was measured as individuals per square metre. A total of 11 limpet species were recorded. Dwesa-Cwebe Nature Reserve exhibited the highest diversity (10 species), followed by Nqabara (9), Presley’s Bay (8), and Hluleka Nature Reserve (6). Limpet abundance and diversity were higher at Dwesa-Cwebe and Nqabara than at Hluleka and Presley’s Bay. These findings suggest that marine reserves may enhance protection of certain species but do not necessarily increase overall species diversity. Clear conservation objectives are therefore essential when establishing marine reserves.